Pengaruh Metode Jartik (Jarimatika) dalam Pembelajaran Daring Terhadap Hasil Belajar Perkalian Siswa Kelas II Sekolah Dasar - Febrianti, Tiwi; Tiurlina, Tiurlina; Alfarisa, Fitri (Didaktika, 2021)
The low numeracy ability of student in elementary schools is focus problem in this study, particularly on multiplication theory during online learning. In addition, the inadequate use of methods in online multiplication learning has resulted in low student. This study aimed to determine the distinctions in the multiplication learning result of grade 2nd elementary school student after using Jarimatika method in online learning. This study is a quantitative with the experimental method by control group design. The number of samples is 20 students of class 2 A as the experimental group and 20 students of class 2 B as the control group. Tests and observations are the data collections technique is used. Based on the result of the hypothesis test by the Man Whitney test with the SPSS version 25 application, Sig value is obtained. (2-tailed) 0.165 0.05. This value states that the result of null hypothesis (H0) proposed by the researcher are accepted and the alternative hypothesis (H1) is rejected. It means that is no distinction in multiplication learning result of grade 2nd elementary school students who use the Jarimatika method in online learning even though there is improvement in students’ scores.